Management of Irritable Bowel Syndrome in the Elderly - Indra Kurniawan; Marcellus S Kolopaking (Acta Medica Indonesiana)
Irritable bowel syndrome (IBS) is one of the most commonly encountered functional gastrointestinal disorders in the elderly. IBS is characterized by abdominal pain and altered bowel habits in the absence of specific organic pathology. The diagnosis of IBS usually depends primarily on established clinical criteria. Currently, Rome III criteria are the criteria of choice for defining IBS. However, aging itself is categorized as one of the alarm symptoms in the diagnosis of IBS that may warrant further investigation. Therefore, exclusion of organic diseases, using several investigations, is of paramount important in the older patients. In general, the treatment of IBS in the elderly is not different from the younger populations. However, greater caution needs to be considered before treating with drugs because of the altered risk-benefit profile in the elderly. Several studies have shown a strong relationship of IBS with psychiatric conditions. Thus, psychological treatments should also be considered in the management of IBS in the elderly.